Multi-analyte biochip (MAB) based on all-solid-state Ion-selective electrodes (ASSISE) for Physiological Research - Wan Salim, Wan Wardatul Amani; Zeitchek, Michael Anthony; Hermann, Andrew C.; Ricco, Antonio J.; Tan, Ming; Selch, Florian; Fleming, Erich D..; Bebout, Brad M.; Bader, Mamoun M.; Ul Haque, Aeraj; Porterfield, David Marshall (2013)
Lab-on-a-chip (LOC) applications in environmental, biomedical, agricultural, biological, and spaceflight research require an ion-selective electrode (ISE) that can withstand prolonged storage in complex biological media 1-4. An all-solid-state ion-selective-electrode (ASSISE) is especially attractive for the aforementioned applications. The electrode should have the following favorable characteristics: easy construction, low maintenance, and (potential for) miniaturization, allowing for batch processing. A microfabricated ASSISE intended for quantifying H+ , Ca2+, and CO32- ions was constructed. It consists of a noble-metal electrode layer (i.e. Pt), a transduction layer, and an ion-selective membrane (ISM) layer. The transduction layer functions to transduce the concentration-dependent chemical potential of the ion selective membrane into a measurable electrical signal. The lifetime of an ASSISE is found to depend on maintaining the potential at the conductive layer/membrane interface 5-7. To extend the ASSISE working lifetime and thereby maintain stable potentials at the interfacial layers, we utilized the conductive polymer (CP) poly(3,4-ethylenedioxythiophene) (PEDOT) 7-9 in place of silver/silver chloride (Ag/AgCl) as the transducer layer. We constructed the ASSISE in a lab-ona chip format, which we called the multi-analyte biochip (MAB) (Figure 1). Calibrations in test solutions demonstrated that the MAB can monitor pH (operational range pH 4-9), CO32- (measured range 0.01 mM - 1 mM), and Ca2+ (log-linear range 0.01 mM to 1 mM). The MAB for pH provides a near-Nernstian slope response after almost one month storage in algal medium. The carbonate biochips show a potentiometric profile similar to that of a conventional ion-selective electrode. Physiological measurements were employed to monitor biological activity of the model system, the microalga Chlorella vulgaris. The MAB conveys an advantage in size, versatility, and multiplexed analyte sensing capability, making it applicable to many confined monitoring situations, on Earth or in space.